The Education of Citizenship, Morality and Civility in the Second Constitutional Period: The Texbooks of Malumat-i Medeniye - Yasar, Fatma Tunc (ISTANBUL 29 MAYIS UNIV & ISAM, 2018)
Among the important goals of the educational reforms during the Second Constitutional Period were to educate the future adults/citizens of the Empire by providing them moral, social, civil and economic skills and values. Accordingly, immediately after the declaration of the Second Constitution a new course, called Malumat-i Medeniye, dealing with subjects such as citizenship, morality and civility, was introduced to the ibtidaiye, rusdiye, idadiye and sultaniye school curricula. The course Malumat-i Medeniye outlined the political elite's modernization project of the Second Constitutional Period. In this article, the textbooks prepared for the course of Malumat-i Medeniye and published with the approval of Ministry of Education are examined within the context of educational programs and the political agenda of the period. For this reason it will analyze the aims, subjects and agendas of this course by looking at the content of the textbooks, curriculum instructions, course programs and relevant discussions in the periodicals.
Keywords: Second Constitution; citizenship; morality; civility; curriculum; textbook; TEXTBOOKS; History; Asian Studies